Sagino procumbentis-Sibthorpietum europaeae, a new association within Montio fontanae-Cardaminetea amarae from Northwestern Portugal - Honrado, Joao; Alves, Paulo; Barreto Caldas, Francisco (Lazaroa, 2003)
A new association (Sagino procumbentis-Sibthorpietum europaeae) of spring vegetation (Montio fontanae-Cardaminetea armarae) is described from temperate submediterranean areas of Northwestern Portugal in order to include perennial herbaceous formations predominated by Sagina procumbens and Sibthorpia europaea. In this paper we present floristic, synecological and biogeographical evidence to support our proposal of this new syntaxon.